FAUNA IKAN DI PERAIRAN DANAU RAWA GAMBUT DI BARITO SELATAN KALIMANTAN TENGAH [Fish fauna in peat swamp lake in South Barito, Central Kalimantan] - Syarifah Nurdawati; Husnah Asyari; Eko Prianto (Jurnal Iktiologi Indonesia, 2007)
Research on fish fauna in peat swamp was conducted in May 2005 representing dry season and in December 2005 representing rainy season as a mean to describe fish species living in peat swamp. Survey location was in Sababilah Lake, Raya Lake and Ganting Lake. There were 56 species in Sababilah Lake, 27 species in Raya Lake and 51 species in Ganting Lake. Each lake had typical species i.e. Cyclocheilichthys janthochir in Raya Lake, Hemirhampodhon tengah, Luciocephalus pulcher, Ompok weberi and Mystus olyroides in Sababilah Lake. Dominant species were Channa pleuropthalmus in Raya Lake, Belontia hasselti, Channa bankanensis) in Sababilah Lake, and Leptobarbus melanopterus Key and Thynnichthys polylepis) in Ganting Lake.